1994
DOI: 10.1016/s0022-5223(94)70332-9
|View full text |Cite
|
Sign up to set email alerts
|

Prolonging myocardial preservation with a modified University of Wisconsin solution containing 2,3-butanedione monoxime and calcium

Abstract: solution is an effective preservative for cold storage of the cardiac aUograft. In an earlier study we showed that addition of calcium and 2,3-butanedione monoxime, a reversible inhibitor of myocardial contracture, further improved preservation of the rabbit heart. In this study we investigated the foUowing: (1) the effects of different concentrations of 2,3-butanedione monoxime and calcium on function of the preserved rabbit heart, (2) how heart preservation is affected when 2,3-butanedione monoxime and calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…BDM, an uncoupling agent, is used in many slicing protocols (e.g., Watson et al, 2017 ), and preparations of cardiac muscle strips ( Mulieri et al, 1989 ) to reduce tissue damage. BDM is also used to improve cardiac and skeletal muscle function after long cold-storage periods ( Stringham et al, 1994 ; van der Heijden et al, 2000 ) and to reduce reperfusion injury ( Voigtlander et al, 1999 ). All processing steps were performed on a cooled plate on a laminar flow workbench.…”
Section: Methodsmentioning
confidence: 99%
“…BDM, an uncoupling agent, is used in many slicing protocols (e.g., Watson et al, 2017 ), and preparations of cardiac muscle strips ( Mulieri et al, 1989 ) to reduce tissue damage. BDM is also used to improve cardiac and skeletal muscle function after long cold-storage periods ( Stringham et al, 1994 ; van der Heijden et al, 2000 ) and to reduce reperfusion injury ( Voigtlander et al, 1999 ). All processing steps were performed on a cooled plate on a laminar flow workbench.…”
Section: Methodsmentioning
confidence: 99%
“…While our respiratory trials show no significant difference between the two chloride substitutes, there may be certain advantages of using one over the other. For example, lactobionate may possess several beneficial properties for mitochondria [ 18 , 70 ]. Lactobionate also has calcium-chelating properties, which helped decrease calcium contamination levels in buffer B2 without EGTA [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobionate also has calcium-chelating properties, which helped decrease calcium contamination levels in buffer B2 without EGTA [ 20 , 22 ]. And prior research has found that lactobionate acts to decrease cellular injury in preserved tissue for organ transplantation, but the mechanism has yet to be demonstrated [ 18 , 70 ]. In addition to lower chloride concentrations, the lactobionate- and gluconate-based buffers could also improve mitochondrial function by favoring a more condensed, energy-transducing, mitochondrial state associated with ADP stimulated respiration [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these theoretical considerations, there is strong evidence from various experimental settings that adjunctive application of BDM to cardioplegic solutions is beneficial. 4,10,11 Contraction uncoupling during initial postischemic reperfusion by BDM has been equally effective when applied over a 20-minute period in a dosage of 20 mmol/L. 9 The drug is fast acting and its effects are fully reversible within minutes.…”
Section: Discussionmentioning
confidence: 99%